A scoring system for the diagnosis of non-alcoholic steatohepatitis from liver biopsy - Kyoungbun Lee (Journal of Pathology and Translational Medicine, 2020)
Background Liver biopsy is the essential method to diagnose non-alcoholic steatohepatitis (NASH), but histological features of NASH are too subjective to achieve reproducible diagnoses in early stages of disease. We aimed to identify the key histological features of NASH and devise a scoring model for diagnosis. Methods Thirteen pathologists blindly assessed 12 histological factors and final histological diagnoses (‘not-NASH,’ ‘borderline,’ and ‘NASH’) of 31 liver biopsies that were diagnosed as non-alcoholic fatty liver disease (NAFLD) or NASH before and after consensus. The main histological parameters to diagnose NASH were selected based on histological diagnoses and the diagnostic accuracy and agreement of 12 scoring models were compared for final diagnosis and the NAFLD Activity Score (NAS) system. Results Inter-observer agreement of final diagnosis was fair (κ = 0.25) before consensus and slightly improved after consensus (κ = 0.33). Steatosis at more than 5% was the essential parameter for diagnosis. Major diagnostic factors for diagnosis were fibrosis except 1C grade and presence of ballooned cells. Minor diagnostic factors were lobular inflammation (≥ 2 foci/ × 200 field), microgranuloma, and glycogenated nuclei. All 12 models showed higher inter-observer agreement rates than NAS and post-consensus diagnosis (κ = 0.52–0.69 vs. 0.33). Considering the reproducibility of factors and practicability of the model, summation of the scores of major (× 2) and minor factors may be used for the practical diagnosis of NASH. Conclusions A scoring system for the diagnosis of NAFLD would be helpful as guidelines for pathologists and clinicians by improving the reproducibility of histological diagnosis of NAFLD.